Preparation of a tumor-targeted drug-loading material, amphiphilic peptide P10, and analysis of its anti-tumor activity - Ge, Fei; Qiao, Qianqian; Zhu, Longbao; Li, Wanzhen; Song, Ping; Zhu, Longlong; Tao, Yugui; Gui, Lin (Journal of materials science. Materials in medicine, 2019)
A new tumor-targeted drug-loading material, the amphiphilic peptide DGRGGGAAAA (P10) was designed and synthesized, and its self-assembly behavior, drug-loading effects and in vitro characteristics were studied. P10 was synthesized by solid-state synthesis and doxorubicin (DOX) was loaded via dialysis. P10 and DOX were mixed with a mass ratio of 6:1 to form regular round spheres. The interconnection between groups was analyzed spectroscopically and the sphere morphology was studied with SEM and a zeta particle size analyzer. Fluorescence spectroscopy was used to analyze the ability of P10 to form micelles and the efficiency of micelle entrapment, and the drug-loading ratio and drug release characteristics were detected. Finally, the in vitro antitumor activity of P10 was studied with HeLa cells as a model. The results showed that P10’s critical micelle concentration (CMC) value and its average grain diameter were approximately 0.045 mg/L and 500 nm. The micelle entrapment ratio and drug-loading ratio were 23.011 ± 2.88 and 10.125 ± 2.62%, respectively, and the in vitro drug-releasing properties of P10 were described by the Zero-order model and the Ritger-Peppas model. Compared with DOX, P10-DOX had a higher tumor cell inhibition ratio and a dose-effect relationship with concentration. When P10-DOX’s concentration was 20 μg/mL, the inhibition ratio was 44.17%. The new amphiphilic peptide designed and prepared in this study could be a tumor-targeted drug-loading material with better prospects for application. In this paper, a new tumor-targeted drug-loading material, the amphiphilic peptide DGRGGGAAAA (P10) is designed and synthesized, and its self-assembly behavior, drug-loading effects and in vitro characteristics are studied, providing a theoretical basis and design ideas for further studies and the development of targeted drug-loading materials on tumor cells.